Pengaruh Seruan Boikot Produk Pro-Israel terhadap Pembelian Produk Alternatif Mahasiswa Ekonomi Syariah - Nur Fadhillahtul Jam'iyyah; Mustatho', Mustatho'; Miftakhul Rizal Mubaidilla (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
This study aims to determine how much influence the call for a boycott of pro-Israel products on social media has on the decision to purchase alternative products among students of the Islamic Economics study program. This type of research is field research using a quantitative approach. This study uses data collection techniques that complement each other, namely the questionnaire technique to obtain research data by scoring from respondents, then the observation technique to directly observe student purchasing activities that take place, both on campus and off campus, then the documentation technique to obtain some supporting data that is also needed in this study. From the results of the calculation using the formula, a constant number of 9.860 and a regression coefficient of 0.780 are obtained so that the form of the regression equation is Y = 9.860 + 0.780X. So, the call for a boycott of pro-Israel products on social media has a positive effect on the decision to purchase alternative products among students of the Islamic Economics study program at STAI Sangatta. The regression equation is used to predict how strong and how much influence the call for a boycott of pro-Israel products has on the decision to purchase alternative products among students of the Islamic Economics study program at STAI Sangatta. The correlation coefficient test produces an R value of 0.825 with an interpretation between 0.800 - 1.000 which means that the correlation of the variable of the call to boycott pro-Israel products on social media to the decision to purchase alternative products is included in the very strong relationship level.